Relationship between Hounsfield Unit in CT Scan and Gray Scale in CBCT - Tahmineh Razi; Mahdi Niknami; Fakhri Alavi Ghazani (Tabriz University of Medical Sciences, 2014)
Background and aims. Cone-beam computed tomography (CBCT) is an imaging system which has many advantages over computed tomography (CT). In CT scan, Hounsfield Unit (HU) is proportional to the degree of x-ray attenuation by the tissue. In CBCT, the degree of x-ray attenuation is shown by gray scale (voxel value). The aim of the present study was to investigate the relationship between gray scale in CBCT) and Hounsfield Unit (HU) in CT scan. Materials and methods. In this descriptive study, the head of a sheep was scanned with 3 CBCT and one medical CT scanner. Gray scales and HUs were detected on images. Reconstructed data were analyzed to investigate relationship between CBCT gray scales and HUs. Results. A strong correlation between gray scales of CBCT and HUs of CT scan was determined. Conclusion. Considering the fact that gray scale in CBCT is the criteria in measurement of bone density before implant treatments, it is recommended because of the lower dose and cost compared to CT scan.